Role of Protein Mannosylation in the Candida tropicalis-Host Interaction - Hernández-Chávez, Marco J.; Clavijo-Giraldo, Diana M.; Novák, Ádám; Lozoya-Pérez, Nancy E.; Martínez-Álvarez, José A.; Salinas-Marín, Roberta; Hernández, Nahúm V.; Martínez-Duncker, Iván; Gácser, Attila; Mora-Montes, Héctor M. (Frontiers in Microbiology, 2019)
Mannans are components of the fungal wall attached to proteins via N- or O-linkages. In Candida albicans, Och1 is an α1,6-mannosyltransferase that adds the first mannose unit to the N-linked mannan outer chain; whereas Pmr1 is an ion pump that imports Mn2+ into the Golgi lumen. This cation is the cofactor of Golgi-resident mannosyltransferases, and thus Pmr1 is involved in synthesis of both N- and O-linked mannans. Since we currently have limited information about the genetic network behind the Candida tropicalis protein mannosylation machinery, we disrupted OCH1 and PMR1 in this organism. The C. tropicalis pmr1Δ and och1Δ mutants showed increased doubling times, aberrant colony and cellular morphology, reduction in the wall mannan content, and increased susceptibility to wall perturbing agents. These changes were accompanied with increased exposure of both β1,3-glucan and chitin at the wall surface of both mutant strains. Our results showed that O-linked mannans are dispensable for cytokine production by human mononuclear cells, but N-linked mannans and β1,3-glucan are key ligands to trigger cytokine production in a co-stimulatory pathway involving dectin-1 and mannose receptor. Moreover, we found that the N-linked mannan core found on the surface of C. tropicalis och1Δ null mutant was capable of inducing cytokine production; and that a mannan-independent pathway for IL-10 production is present in the C. tropicalis-mononuclear cell interaction. Both mutant strains showed virulence attenuation in the Galleria mellonella and the mouse model of systemic candidiasis. Therefore, mannans are relevant for cell wall composition and organization, and for the C. tropicalis-host interaction.